Transformasi Mahasiswa Pendidikan Agama Islam Menjadi Pendidik Profesional dengan Sembilan Dasar Keterampilan Mengajar - Ahmad Ibnu Aqil Assaidi; Alfiatus Syarifah; Mutia Dwi Astutik; Wildatul Jennah; Abdullah Hasan Jauhari; Ismail Wahid (Lembaga Einstein College (LEC), 2025)
This study aims to examine the transformation of Islamic Education (PAI) students into professional educators through the mastery of nine fundamental teaching skills. The research is driven by the challenges faced by PAI students in balancing Islamic theoretical knowledge with practical teaching abilities, as well as the urgent need to develop competent and character-driven teachers. The method used in this study is library research, by analyzing various academic literatures related to teaching skills, educator professionalism, and Islamic education. The subjects of this study are PAI students as future religious educators who will play a vital role in shaping students' character and spirituality. The findings indicate that mastering the nine basic teaching skills—including the ability to open and close lessons, explain materials, ask questions, provide reinforcement, and manage classrooms greatly contributes to shaping PAI students into professional educators. Moreover, integrating Islamic values into teaching practices strengthens students’ religious character. Training programs, field practice, and self-development initiatives such as micro teaching and the Teaching Campus program are essential strategies to prepare PAI students to become competent, inspiring, and contextually relevant educators